2004
DOI: 10.1086/427799
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Absorption Features in the X-Ray Spectrum of the Narrow-Line Quasar PG 1404+226: Possible Evidence of Accretion Disk Winds

Abstract: We present the results of an analysis of data from XMM-Newton and Chandra observations of the highluminosity narrow-line quasar PG 1404ϩ226. We confirm a strong soft X-ray excess in the X-ray spectrum, and we find rapid variability (a factor of 2 in about 5000 s). When the X-ray spectrum is fitted with a two-component model that includes a power-law and a blackbody component, we find that low-energy absorption lines are required to fit the data. If we interpret these lines as due to highly ionized species of h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 9 publications
1
20
1
Order By: Relevance
“…Recently, Dasgupta et al (2004) reported the discovery of analogous features in the XMM spectrum of the narrow emission line quasar PG 1404+226. Similar results for this object and two other NLS1 galaxies, 1H 0707-495 and IRAS 13224-3809, were presented earlier from ASCA observations by Leighly et al (1997).…”
Section: Introductionmentioning
confidence: 97%
“…Recently, Dasgupta et al (2004) reported the discovery of analogous features in the XMM spectrum of the narrow emission line quasar PG 1404+226. Similar results for this object and two other NLS1 galaxies, 1H 0707-495 and IRAS 13224-3809, were presented earlier from ASCA observations by Leighly et al (1997).…”
Section: Introductionmentioning
confidence: 97%
“…The geometry and the position of these warm absorbers are uncertain. Some AGNs show evidence for highvelocity outflows (e.g., Chartas et al 2002;Reeves et al 2003Reeves et al , 2008Dadina & Cappi 2004;Dasgupta et al 2005;Markowitz et al 2006;Braito et al 2007;Cappi et al 2009). Moreover with the aid of high-resolution, narrowband imaging (or integral field spectroscopy) and Hubble Space Telescope imaging, it was possible to identify extended regions of highly ionized material around the central engine also known as "ionization cones" with a size of a few up to 15-20 kpc which suggests an anisotropic escape of photons from AGNs confined to a cone by a dusty torus (Wilson et al 1993).…”
Section: Introductionmentioning
confidence: 99%
“…In some AGNs, high-velocity outflows have also been detected (e.g., Reeves et al 2003; Dadina & Cappi 2004;Dasgupta et al 2005;Braito et al 2007). The resulting mass outflow rate can be a substantial fraction of the accretion rate required to power the AGN.…”
Section: Introductionmentioning
confidence: 99%